Negotiation of Meaning and Language Acquistion by Indonesia EFL Learners - Hery Hery (TEFLIN Journal: A publication on the teaching and learning of English, 2001)
This study was aimed at investigating negotiation of meaning among Indonesian learners of EFL in English interaction. It was also intended to examine which type of tasks stimulate the learners to negotiate meaning. Forty undergraduate students were involved in this study. Information gap, jigsaw, and role-play tasks were given to students for dyadic interactions. The results show that the information gap tasks were more productive than the other two types of tasks. The study also shows that more interaction and negotiation of meaning were produced by the learners in the same gender and the same proficiency dyads when they were assigned the information gap and jigsaw tasks.